Ecotourism Strategy and Potential of Delleng Simpon, Ulumerah, Pakpak Bharat Regency - Munthe, Muhtar Ardansah; Sari, Ratna; Daulay, Aulia Putra (Jurnal Pijar Mipa, 2024)
Ecotourism can be developed into a sustainable development model because its management concept is oriented to the economy and maintaining forest preservation and community empowerment. Delleng Simpon is a forest area with a beautiful panoramic expanse. The Delleng Simpon area is critical and has the potential to be developed. This study aims to find strategies and potentials in the management of Delleng Simpon ecotourism by considering the community's ecological, economic, and socio-cultural conditions. This research used the qualitative descriptive case study method. Data collection was carried out through surveys and interviews in the field. The data was analyzed using the SWOT method. The analysis results showed that (42%) of respondents were not involved in tourism management because ecotourism is managed directly by the Tourism Office, visitor participation in maintaining cleanliness is still low, and only (14%) always dispose of garbage in its place. Respondents' perceptions of ecotourism development, including access, facilities, cleanliness, and promotion, are still less than optimal; all respondents agreed to build public facilities and support facilities immediately. The SWOT analysis results for the Delleng Simpon ecotourism development strategy are in Quadrant I by implementing the Strength-Opportunities (SO) strategy. The priority of the SO's strategy is the development of ecotourism by involving more local communities; its management must be carried out with the principles of preserving the environment, increasing educational value, and maximizing local wisdom.